2018
DOI: 10.1111/ejn.13987
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness and volume abnormalities in Internet gaming disorder: Evidence from comparison of recreational Internet game users

Abstract: Although online gaming may lead to Internet gaming disorder (IGD), most players are recreational game users (RGUs) who do not develop IGD. Thus far, little is known about brain structural abnormalities in IGD subjects relative to RGUs. The inclusion of RGUs as a control group could minimize the potential effects of gaming experience and gaming-related cue familiarity on the neural mechanism of IGD subjects. In this study, structural magnetic resonance imaging data were acquired from 38 IGD subjects and 66 RGUs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 69 publications
(99 reference statements)
1
29
0
3
Order By: Relevance
“…Decreased cortical thickness in brain regions that are involved in cognitive control, decision making, and reward/loss processing (OFC, inferior parietal lobe, cuneus, precentral gyrus, and right middle temporal gyrus) was reported in IGD compared with recreational internet game use. 22 Finally, adolescents with IGD showed decreased cortical thickness in distributed cerebral areas and had a positive correlation between the left insular cortical thickness and symptom severity. 23 …”
Section: Cortical Thicknessmentioning
confidence: 92%
“…Decreased cortical thickness in brain regions that are involved in cognitive control, decision making, and reward/loss processing (OFC, inferior parietal lobe, cuneus, precentral gyrus, and right middle temporal gyrus) was reported in IGD compared with recreational internet game use. 22 Finally, adolescents with IGD showed decreased cortical thickness in distributed cerebral areas and had a positive correlation between the left insular cortical thickness and symptom severity. 23 …”
Section: Cortical Thicknessmentioning
confidence: 92%
“…There is increasing evidence that, in its extreme, excessive media usage can also lead to behavioral addiction, This seems to be particularly the case for internet gaming. Studies examining the neuronal consequences of internet gaming disorder reported numerous significant changes (99,100), including alterations in resting-state EEG coherence (101), significant alterations in cortical thickness (102,103), altered functional connectivity in the default mode network (104,105), and significant associations with ADHD and other psychiatric disorders (106,107). As they now stand, these findings are correlational and cannot establish causation.…”
Section: Studying the Effects Of Media Overusementioning
confidence: 99%
“…Based on previous correlational studies, the brain neurobiology of IGD can be summarized as increased activity within the orbitofrontal cortex and decreased activity within the dorsolateral prefrontal cortex [9,10]. Kim and Kang [9] found that IGD patients, compared to other gamers, showed a stronger functional connectivity (FC) within the orbitofrontal cortex, which is involved in motivational salience, and a decreased FC within the dorsolateral prefrontal cortex, which is involved in learning and attention.…”
Section: Debates On Internet Gaming Disordermentioning
confidence: 99%
“…Kim and Kang [9] found that IGD patients, compared to other gamers, showed a stronger functional connectivity (FC) within the orbitofrontal cortex, which is involved in motivational salience, and a decreased FC within the dorsolateral prefrontal cortex, which is involved in learning and attention. Additionally, Wang et al [10] reported a decreased cortical thickness within the dorsolateral prefrontal cortex, related to cognitive control, decision making, and reward and loss processing. Motivational salience was thought to be associated with continuous and repetitive behaviors in various addictive diseases [11].…”
Section: Debates On Internet Gaming Disordermentioning
confidence: 99%